Let’s read together: getting close with pediatric patients at Hospital Universiti Sains Malaysia - Engku Chik, Engku Razifah; Hassan, Noraida; Mohd Roni, Nurul Azurah; Wan Mat Alli, Wan Emilin; Ab. Manan, Rabiatul Adawiah; Che Harun, Herman Harianto (Division of Industry and Community Network, Universiti Sains Malaysia, 2016)
Cultivating reading habits among children from the early stage is a big challenge in information age. Reading habits is a starting point to be a literate person; who is able to read and have formal or informal education. Indeed, children’s with healthcare condition needs special support from all parties include parents, caregivers, teachers and hospital administrators to nurture reading habits among them. Bibliotherapy technique has been applied to help pediatric patients in solving problems and coping with life changes by using books or reading materials especially related to their health. This technique will help them to undergo recovery process and treatment from caregivers. Book Buddies project conducted by Hamdan Tahir Library implements this technique on paediatric patients at Hospital USM. The impacts of the project measure via observation, discussion and involvement of pediatric patients in activities scheduled. A mobile library service was introduced as an extended of library services to pediatric patients and guardian. The service will help the needy people to increase knowledge and spend their leisure time with a benefit activity. The number of book loan transactions increased from time to time which is achieved the project’s objectives. May this project will create a good dimension and increase reputation of library and university’s role in the eyes of Malaysian society.